Window Filter (WinTer) To Capture Pollution of Lead (Pb) For Houses Near The Highway To Prevent Health Problems - Rifang Pri Asmara; Fitri Azizah; Siti Umi Afifah (UPT Penerbitan Universitas Jember, 2016)
Lead (Pb) is a chemical element that stable and used in various fields of modern industry, such as an ingredient in paint, batteries, a mixture of gasoline and many more. Lead (Pb) is a material which is very dangerous because it has toxic properties, when entered into the human body will cause some health problems, for example, disorders of the kidneys, brain, and other dangerous disorders. Window filter is a solution to overcome the anxiety experienced by any people. Window filter is a complementary window of the house that has the ability to filter smoke exposure of lead (Pb), so that the community house near the highway to minimize the potential for developing the disease due to lead (Pb). The workings of this product is to filter the smoke of lead even though the window was open so that residents feel comfortable due to the air vents keep it running smoothly. In addition, residents will be prevented from diseases caused by lead (Pb).